Edukasi Senam Otak pada Lansia di Desa Kasang Kumpeh - Wanti Hasmar; Faridah Faridah (Jurnal Abdimas Kesehatan (JAK), 2022)
Elderly is someone who has reached the age of 60 years and over. Elderly is a term for someone who has entered the period of late adulthood or old age. Brain exercise is a series of simple movements that can balance every part of the brain, can draw out the concentration level of the brain, and also as a way out for the blocked part of the brain to function optimally. Community service activities are carried out from September to December 2021 by providing brain exercise movement leaflets consisting of 4 brain exercise movements consisting of (1) Cross / Cross Movement, (2) Hooks Up, (3) Lazy Eight, (4) Neck Rotation and demonstration of the movement to the elderly in Kasang Kumpeh Village. This community service aims to be used as a source of knowledge and brain exercises for the elderly in Kasang Kumpeh Village can be carried out. The results of the evaluation both through questions and answers and demonstrations of the brain gymnastics movements are that on average the elderly can perform brain gymnastics movements even though errors often occur in every movement, so that they can improve cognitive function in the elderly.